Association between hypermethylation of DNA repetitive elements in white blood cell DNA and pancreatic cancer - Neale, R.; Clark, P.; Fawcett, J.; Fritschi, Lin; Nagler, B.; Risch, H.; Walters, R.; Crawford, W.; Webb, P.; Whiteman, D.; Buchanan, D. (Elsevier Inc., 2014)
Pancreatic cancer is a leading cause of cancer-related deaths worldwide. Methylation of DNA may influence risk or be a marker of early disease. The aim of this study was to measure the association between methylation of three DNA repetitive elements in white blood cell (WBC) DNA and pancreatic cancer. DNA from WBCs of pancreatic cancer cases (n = 559) and healthy unrelated controls (n = 603) were tested for methylation of the LINE-1, Alu and Sat2 DNA repetitive elements using MethyLight quantitative PCR assays. Odds ratios (ORs) and 95% confidence intervals (95%CI) between both continuous measures of percent of methylated sample compared to a reference (PMR) or quintiles of PMR and pancreatic cancer, adjusted for age, sex, smoking, BMI, alcohol and higher education, were estimated. The PMR for each of the three markers was higher in cases than in controls, although only LINE-1 was significantly associated with pancreatic cancer (OR per log unit = 1.37, 95%CI = 1.16–1.63). The marker methylation score for all three markers combined was significantly associated with pancreatic cancer (p-trend = 0.0006). There were no associations between measures of PMR and either presence of metastases, or timing of blood collection in relation to diagnosis, surgery, chemotherapy or death (all p > 0.1). We observed an association between methylation of LINE-1 in WBC DNA and risk of pancreatic cancer. Further studies are needed to confirm this association.